A High-Throughput Screening Triage Workflow to Authenticate a Novel Series of PFKFB3 Inhibitors. (January 2018) - St-Gallay, Stephen A.; Bennett, Neil; Critchlow, Susan E.; Curtis, Nicola; Davies, Gareth; Debreczeni, Judit; Evans, Nicola; Hardern, Ian; Holdgate, Geoff; Jones, Neil P.; Leach, Lindsey; Maman, Sarita; et al.
A high-throughput screen (HTS) of human 6-phosphofructo-2-kinase/fructose-2, 6-biphosphatase 3 (PFKFB3) resulted in several series of compounds with the potential for further optimization. Informatics was used to identify active chemotypes with lead-like profiles and remove compounds that commonly occurred as actives in other HTS screens. The activities were confirmed with IC50 measurements from two orthogonal assay technologies, and further analysis of the Hill slopes and comparison of the ratio of IC50 values at 10 times the enzyme concentration were used to identify artifact compounds. Several series of compounds were rejected as they had both high slopes and poor ratios. A small number of compounds representing the different leading series were assessed using isothermal titration calorimetry, and the X-ray crystal structure of the complex with PFKFB3 was solved. The orthogonal assay technology and isothermal calorimetry were demonstrated to be unreliable in identifying false-positive compounds in this case. Presented here is the discovery of the dihydropyrrolopyrimidinone series of compounds as active and novel inhibitors of PFKFB3, shown by X-ray crystallography to bind to the adenosine triphosphate site. The crystal structures of this series also reveal it is possible to flip the binding mode of the compounds, and the alternative orientation can be driven by a sigma-hole interaction between an aromatic chlorine atom and a backbone carbonyl oxygen. These novel inhibitors will enable studies to explore the role of PFKFB3 in driving the glycolytic phenotype of tumors.